LITERATURE OF REVIEW THE INFLUENCE OF SUPERIOR LEADERSHIP AND JOB STRESS ON EMPLOYEE PERFORMANCE AT THE INDONESIAN BINTANG COFFEE COMPANY (TOMORO COFFEE) - Mutiara Salsabilla Zonia (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research is a literature review that will examinethe influence of superior leadership and job stress onemployee performance. This research focuses onemployee performance at the Indonesian BintangCoffee (Tomoro Coffee) company. This research usesa quantitative design that uses numbers for decisionmaking. The population of this research is employeesat Tomora Coffee. The data collected will be testedusing statistical tools to obtain conclusions from theresearch results.